2020
DOI: 10.1021/acs.orglett.0c03732
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Strategies for the π-Extension of Heteroaryl Halides Using Norbornadiene as an Acetylene Synthon

Abstract: Pd-catalyzed multicomponent coupling reactions of five-membered heteroaryl halides and norbornadiene (NBD) were developed. Either direct addition of (benzo)­azoles or 2:1 annulation was achieved depending on the propensity of the intermediate complex to undergo palladacycle formation, determined by the nature and substitution pattern of the heteroarene. The obtained exo- and cis-diheteroaryl norbornenes underwent epimerization and retro-Diels–Alder reactions to afford the corresponding trans-isomers and π-exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…Recently, we demonstrated that the incorporation of NBD as an acetylene synthon led to the benzannulation of five‐membered heteroarenes through a Pd‐catalyzed cyclization followed by a retro‐Diels‐Alder reaction (Figure 2B, top) [12] . In addition to the Pd‐catalyzed 1:2 coupling reaction between heteroaryl halides and NBD, a 2:1 coupling reaction was developed to synthesize polycyclic heteroaromatic systems (Figure 2B, middle) [13] . Consequently, it was considered that C4(C7)‐substituted benzofused heteroarenes could arise from alkynyl norbornene derivatives, through a simultaneous retro‐Diels‐Alder reaction of the norbornene ring, which results in π‐conjugated structures (Figure 2B, bottom).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that the incorporation of NBD as an acetylene synthon led to the benzannulation of five‐membered heteroarenes through a Pd‐catalyzed cyclization followed by a retro‐Diels‐Alder reaction (Figure 2B, top) [12] . In addition to the Pd‐catalyzed 1:2 coupling reaction between heteroaryl halides and NBD, a 2:1 coupling reaction was developed to synthesize polycyclic heteroaromatic systems (Figure 2B, middle) [13] . Consequently, it was considered that C4(C7)‐substituted benzofused heteroarenes could arise from alkynyl norbornene derivatives, through a simultaneous retro‐Diels‐Alder reaction of the norbornene ring, which results in π‐conjugated structures (Figure 2B, bottom).…”
Section: Figurementioning
confidence: 99%
“…[12] In addition to the Pd-catalyzed 1:2 coupling reaction between heteroaryl halides and NBD, a 2:1 coupling reaction was developed to synthesize polycyclic heteroaromatic systems (Figure 2B, middle). [13] Consequently, it was considered that C4(C7)-substituted benzofused heteroarenes could arise from alkynyl norbornene derivatives, through a simultaneous retro-Diels-Alder reaction of the norbornene ring, which results in π-conjugated structures (Figure 2B, bottom). This approach provides increased accessibility to the cyclization precursors prepared by Pd-catalyzed three-component reactions, using readily available heteroaryl halides, NBD, and terminal alkynes in one step (Scheme 1).…”
mentioning
confidence: 99%
“…75 The use of bromopyrazoles and TBAI was optimal for the three-component reaction with 1,3-azoles (Scheme 20). 3 Similar to the 1:2 coupling, the addition of two heteroarenes to NBD was exo-and syn-selective. Therefore, the presence of two heteroarene rings on the same side creates a steric effect, and epimerization readily occurs to afford the corresponding trans-isomer in N,N-dimethylacetamide (DMA).…”
Section: Three-component Couplingmentioning
confidence: 95%
“…M. Jeong, S. Kim, E. Kim, M. Hwang, Y. J. Padhi, B. Choi, J. Lee, Y. Joo, J. M. Org. Lett.20202296709676 …”
Section: Key Referencesmentioning
confidence: 99%
See 1 more Smart Citation